2021
DOI: 10.3390/en14206766
|View full text |Cite
|
Sign up to set email alerts
|

Grid Forming Stator Flux Control of Doubly-Fed Induction Generator

Abstract: The doubly fed induction generator is widely used in wind power applications. For stand-alone operation of this machine, the control of the stator flux with fixed voltage and frequency has been proposed. This paper extends the stator flux control of the doubly fed induction machine by droop mechanisms, which vary the setpoint of flux magnitude and frequency depending on active and reactive power. This gives the doubly fed induction generator system unknown grid supporting and grid forming performance. The vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…A comprehensive review of PC techniques for islanded MGs is presented in [270]. In [271], it was shown that wind energy plants equipped with doubly fed induction generators can achieve excellent grid forming and grid supporting capabilities using stator flux control with droops for frequency and magnitude. The idea of adaptive dynamic participation factors was presented in [272] to design grid-forming controller for dynamic virtual power plants.…”
Section: A Grid Formation In Vppsmentioning
confidence: 99%
“…A comprehensive review of PC techniques for islanded MGs is presented in [270]. In [271], it was shown that wind energy plants equipped with doubly fed induction generators can achieve excellent grid forming and grid supporting capabilities using stator flux control with droops for frequency and magnitude. The idea of adaptive dynamic participation factors was presented in [272] to design grid-forming controller for dynamic virtual power plants.…”
Section: A Grid Formation In Vppsmentioning
confidence: 99%
“…with modified normalized DFIM angular velocity Ω m,H0 defined in the following, see (18). Assuming Ω m,H0 = Ω m in (17), M m,ref decreases if the rotor decelerates, counteracting the desired inertial response [6,24]. A simple MPPT compensation is to sample and hold the MPPT input when detecting active inertia emulation, i. e.…”
Section: Maximum Power Point Tracking and Its Compensationmentioning
confidence: 99%
“…However, this control is not based on the VSM concept and it is not stated, how to adapt the gains for different DFIM operating points. Moreover, [17] does not achieve decoupling of the responses to grid frequency changes and to power reference changes, as proposed in this paper.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations